Dopaminergic modulation of affective and social deficits induced by prenatal glucocorticoid exposure - Borges, Sónia Maria de Sousa (2013)
Prenatal stress or exposure to elevated levels of glucocorticoids (GCs) can impair specific neurobehavioral circuits leading to alterations in emotional processes later in life. In turn, emotional deficits may interfere with the quality and degree of social interaction. Here, by using a comprehensive behavioral approach in combination with the measurement of ultrasonic vocalizations, we show that in utero GC (iuGC)-exposed animals present increased immobility in the forced swimming test, pronounced anhedonic behavior (both anticipatory and consummatory), and an impairment in social interaction at different life stages. Importantly, we also found that social behavioral expression is highly dependent on the affective status of the partner. A profound reduction in mesolimbic dopaminergic transmission was found in iuGC animals, suggesting a key role for dopamine (DA) in the etiology of the observed behavioral deficits. Confirming this idea, we present evidence that a simple pharmacological approach—acute L-3,4-dihydroxyphenylacetic acid (L-DOPA) oral administration, is able to normalize DA levels in iuGC animals, with a concomitant amelioration of several dimensions of the emotional and social behaviors. Interestingly, L-DOPA effects in control individuals were not so straightforward; suggesting that both hypo- and hyperdopaminergia are detrimental in the context of such complex behaviors.